2010
DOI: 10.15283/ijsc.2010.3.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Spheroid Formation of Hepatocytes in Liver Tissue Engineering

Abstract: The liver plays an important role in a broad spectrum of physiological functions and detoxifies endogenous and exogenous substances. The liver failure is associated with a high risk of mortality because it is one of important organs in our body. Various bioartificial liver (BAL) systems have been used for clinical trials as a bridge for liver transplantations in patients with liver failure. Long term and stable liver-specific functions of hepatocytes in the development of BAL support systems should be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This approach has been developed in the research of cancer (7,76,102), stem cells (17,120), and many organs (such as liver, kidney, heart, etc.) (3,16,64,75). The difficulty in growing physiologically similar 3D tissue or organ cultures stems from finding viable cell types, biocompatible scaffold materials, and a scaffold design that supports the development of an ECM and vascularization.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This approach has been developed in the research of cancer (7,76,102), stem cells (17,120), and many organs (such as liver, kidney, heart, etc.) (3,16,64,75). The difficulty in growing physiologically similar 3D tissue or organ cultures stems from finding viable cell types, biocompatible scaffold materials, and a scaffold design that supports the development of an ECM and vascularization.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Accordingly, there have been several reports about the development of in-vitro culture systems for high-functioning hepatocytes37. Spheroid culture of hepatocytes, formed through the rearrangement and compaction of cell aggregates of liver-derived cells including primary hepatocytes or cell lines, yields much higher levels of liver-specific functions than those seen in monolayer culture due to the multiple strong similarities between conditions in spheroid cultures and real tissues, although limitations with respect to the diffusion of oxygen and nutrients into the centers of large spheroids of hepatocytes should be considered38. We also recently reported that primary human hepatocytes as well as HepG2 cells can express higher cell functions when grown in hepatocyte spheroid culture3940.…”
Section: Discussionmentioning
confidence: 99%
“…Reports regarding the biofunctional use of natural polymers in TE scaffolds are currently available . Collagen and HS are the natural components of the liver ECM which immobilize the cells on the substrate via cell adhesion domains onto their molecular chains . The specific amino acid sequence of the collagen protein plays a crucial part in the cell‐scaffold interactions .…”
Section: Introductionmentioning
confidence: 99%
“…7,14 Collagen and HS are the natural components of the liver ECM which immobilize the cells on the substrate via cell adhesion domains onto their molecular chains. [15][16][17] The specific amino acid sequence of the collagen protein plays a crucial part in the cell-scaffold interactions. 17,18 Heparan sulfate (HS) proteoglycans associated with the core protein and sulfate groups are thus formed.…”
Section: Introductionmentioning
confidence: 99%